Second-hand smoking, hypertension and cardiovascular risk: findings from Peru - Antonio Bernabe-Ortiz (BMC, 2021)
Abstract Background Second-hand smoking has not been detailedly studied in Peru, where smoking is prohibited in all indoor workplaces, public places, and public transportation. Second-hand smoke exposure may occur at home or any other places. This study aimed to estimate the prevalence of second-hand smoking and assess its association with hypertension and cardiovascular risk in Peru. Materials and methods Secondary analysis of a nationally-representative population-based survey including individuals aged 18–59 years. There were two outcomes: hypertension and 10-year cardiovascular risk using the Framingham and the 2019 World Health Organization (WHO) risk scores. The exposure was self-reported second-hand smoking during the 7 days before the survey. The association between second-hand smoking and hypertension was quantified with Poisson models reporting prevalence ratio (PR) and 95% confidence interval (95% CI); the association between second-hand smoking and cardiovascular risk was quantified with linear regressions reporting coefficients and their 95% CI. Results Data from 897 individuals, mean age: 38.2 (SD: 11.8) years, and 499 (55.7%) females, were analyzed, with 8.7% subjects reporting second-hand smoking at home and 8.3% at work or any other place. Thus, 144 (15.5%; 95% CI: 12.8%-18.6%) subjects reported any second-hand smoking. In multivariable model second-hand smoking was associated with hypertension (PR = 2.42; 95% CI: 1.25–4.67), and with 1.2% higher Framingham cardiovascular risk, and 0.2% higher 2019 WHO risk score. Conclusions There is an association between second-hand smoking and hypertension as well as with cardiovascular risk, and 15% of adults reported second-hand smoke exposure overall with half of them exposed at home. There is a need to guarantee smoking-free places to reduce cardiovascular risk.